Iron oxide-coupled CRISPR-nCas9-based genome editing assessment in mucopolysaccharidosis IVA mice - Andrés Felipe Leal; Betul Celik; Nidhi Fnu; Shaukat Khan; Shunji Tomatsu; Carlos Javier Alméciga-Díaz (Molecular Therapy: Methods & Clinical Development, 2023)
Mucopolysaccharidosis (MPS) IVA is a lysosomal storage disorder caused by mutations in the GALNS gene that leads to the lysosomal accumulation of keratan sulfate (KS) and chondroitin 6-sulfate, causing skeletal dysplasia and cardiopulmonary complications. Current enzyme replacement therapy does not impact the bone manifestation of the disease, supporting that new therapeutic alternatives are required. We previously demonstrated the suitability of the CRISPR-nCas9 system to rescue the phenotype of human MPS IVA fibroblasts using iron oxide nanoparticles (IONPs) as non-viral vectors. Here, we have extended this strategy to an MPS IVA mouse model by inserting the human GALNS cDNA into the ROSA26 locus. The results showed increased GALNS activity, mono-KS reduction, partial recovery of the bone pathology, and non-IONPs-related toxicity or antibody-mediated immune response activation. This study provides, for the first time, in vivo evidence of the potential of a CRISPR-nCas9-based gene therapy strategy for treating MPS IVA using non-viral vectors as carriers.